Optimization of Distributed Generation Placement and Capacity Using Flower Pollination Algorithm Method - Jimmy Trio Putra; Istiqomah Istiqomah; Syahrial Shaddiq; Agus Diantoro (Jurnal Ilmiah Teknik Elektro Komputer dan Informatika, 2021)
The need for energy, especially electricity is increasing along with the development of technology. An increase in electrical load and the location of the powerplant far causes voltage drops and causes power line losses. One solution can be chosen by adding a distributed generation (DG) to the distribution network. This study aims to enhance the voltage profile and reduce power losses based on the optimal placement and capacity of DG-based photovoltaic (PV) in the Bantul Feeder 05 distribution network. The flower pollination algorithm (FPA) method is used to determine the optimal DG placement and capacity. The study was conducted using three additional DG scenarios, namely scenario 1 with single DG and scenario 2 with multi-DG (2 DG and 3 DG). The results showed that the optimal placement and capacity of DG were on buses 9, 19, and 33 with DG sizes of 1.880 kW, 2.550 kW, and 2.300 kW, respectively. This placement can increase the voltage profile and reduce the active power loss from 439.8 kW to 77.5 kW. The research also considers the increase in the reliability of the distribution system observe by the energy not supplied and cost of energy not supplied index.